Impact of mental disorders on the risk of atrial fibrillation in patients with diabetes mellitus: a nationwide population-based study - Nan Young Bae; So-Ryoung Lee; Eue-Keun Choi; Hyun Jin Ahn; Hyo-Jeong Ahn; Soonil Kwon; Kyung-Do Han; Kyu-Na Lee; Seil Oh; Gregory Y. H. Lip (Cardiovascular Diabetology, 2022)
Abstract Background It is unclear whether mental disorders are an independent risk factor for atrial fibrillation (AF) in patients with diabetes. We aimed to investigate whether patients with diabetes who have mental disorders have an increased risk for AF. Methods Using the Korea National Health Insurance Service database, we enrolled 2,512,690 patients diagnosed with diabetes without AF between 2009 and 2012. We assessed five mental disorders: depression, insomnia, anxiety, bipolar disorder, and schizophrenia. Newly diagnosed AF was identified during the follow-up period, and multivariate Cox regression analysis was performed. Results Among the 2,512,690 patients (mean age 57.2 ± 12.3 years; 60.1% men), 828,929 (33.0%) had mental disorders. Among the five mental disorders, anxiety (68.1%) was the most common, followed by insomnia (40.0%). During a median follow-up duration of 7.1 years, new-onset AF was diagnosed in 79,525 patients (4.66 per 1,000 person-years). Patients with diabetes who had mental disorders showed a higher risk for AF (adjusted hazard ratio [HR] 1.19; 95% confidence interval [CI] 1.17–1.21; p-value < 0.001). Depression, insomnia, and anxiety were significantly associated with higher risk for AF (adjusted HR [95% CI]: 1.15 [1.12–1.17], 1.15 [1.13–1.18], and 1.19 [1.67–1.21], respectively; all p-values < 0.001), whereas bipolar disorder and schizophrenia were not. Conclusions Mental disorders, especially depression, insomnia, and anxiety, were associated with an increased risk for AF in patients with diabetes. Greater awareness with a prompt diagnosis of AF should be considered for patients with both DM and mental disorders.